PENERAPAN MEDIA PETA KONSEP OLEH GURU PPKn PADA MATA PELAJARAN PPKn UNTUK MENINGKATKAN PEMAHAMAN SISWA DIKELAS X IPS 3 SMAN 1 BUKITTINGGI - Tama, Syafreni Putri; Sari, Nila; Khairunnisa, Khairunnisa (STKIP Pesisir Selatan, 2021)
The purpose of this research is to describe the application of concept maps in SMAN 1 Bukittinggi, to identify the effectiveness of the application of concept map media in PPKn learning at SMAN 1 Bukittinggi, and to find out the consequences of using concept map media in improving students' understanding.This type of research is a qualitative descriptive research method in this research, because it corresponds to the nature of the problem as well as the objectives that want to be obtained from its research. Qualitative properties that have in this study require the author to jump directly into the field in finding data or information through observations, interviews, documentation studies. The informants in this study were students, PPKN teachers,Research shows that. (1) The application of concept map media is a medium that supports the effectiveness of pbm itself both teachers and siawa both benefit by using this concept map media. (2) The effectiveness of the application of concept map media in PPKn learning is very effective and able to improve students' understanding because students not only memorize but also understand the material.(3).the consequence of applying the concept map in improving students' understanding in PPKn learning is that there are positive and negative impacts